Qualitative assessment of the primary care outcomes questionnaire: a cognitive interview study - Mairead Murphy; Sandra Hollinghurst; Chris Salisbury (BMC, 2018)
Abstract Background The Primary Care Outcomes Questionnaire (PCOQ) is a new patient-reported outcome measure designed specifically for primary care. This paper describes the developmental process of improving the item quality and testing the face validity of the PCOQ through cognitive interviews with primary care patients. Methods Two formats of the PCOQ were developed and assessed: the PCOQ-Status (which has an adjectival scale) and the PCOQ-Change (which has the same items as the PCOQ-Status, but a transitional scale). Three rounds of cognitive interviews were held with twenty patients from four health centres in Bristol. Patients seeking healthcare were recruited directly by their GP or practice nurse, and others not currently seeking healthcare were recruited from patient participation groups. An adjusted form of Tourangeau's model of cognitive processing was used to identify problems. This contained four categories: general comprehension, temporal comprehension, decision process, and response process. The resultant pattern of problems was used to assess whether the items and scales were working as intended, and to make improvements to the questionnaires. Results The problems identified in the PCOQ-Status reduced from 41 in round one to seven in round three. It was noted that the PCOQ-Status seemed to be capturing a subjective view of health which might not vary with age or long-term conditions. However, as it is designed to be evaluative (measuring change over time) as opposed to discriminative (measuring change between different groups of people), this does not present a problem for validity. The PCOQ-Status was both understood by patients and was face valid. The PCOQ-Change had less face validity, and was misunderstood by three out of six patients in round 1. It was not taken forward after this round. Conclusions The cognitive interviews successfully contributed to the development of the PCOQ. Through this study, the PCOQ-Status was found to be well understood by patients, and it was possible to improve comprehension through each round of interviews. The PCOQ-Change was poorly understood and, given that this corroborates existing research, this may call into question the use of transitional questionnaires generally.